Ecobehavioral Assessment of Paraeducator Behaviors That Support Engagement of Students With Disabilities. (July 2020) - Mason, Rose A.; Wills, Howard P.; Irvin, Dwight; Jia, Fan; Kamps, Debra M.
Due to a shortage of special education teachers and an increase in the number of students with disabilities, the use of paraeducators is common. Paraeducators frequently provide instruction, under the direction of a teacher, to support elementary students with disabilities in elementary school classrooms. However, if and how paraeducators implement foundational instructional strategies is largely unknown (e.g., opportunities to respond [OTR], praise). Likewise, how students with disabilities respond to paraeducators' instructional behaviors is also unknown. With decades of evidence indicating that contextual factors (e.g., group size, activity type) influence interactions between educators and students, we relied on ecobehavioral assessment to measure paraeducators' use of core instructional strategies and students' response in the natural context. Our results indicated a correlation between higher rates of paraeducator-delivered OTRs and praise statements and increased student engagement. Of concern, paraeducators infrequently used core, evidence-based instructional approaches, and students often were not engaged. Findings suggest increased student engagement may depend on professional development efforts aimed at improving paraeducators' implementation of these essential core strategies.